2019
DOI: 10.1101/782904
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid evolution at the Drosophila telomere: transposable element dynamics at an intrinsically unstable locus

Abstract: Background: Drosophila telomeres have been maintained by three families of active transposable elements (TEs), HeT-A, TAHRE and TART, collectively referred to as HTTs, for tens of millions of years.The conservation of this arrangement contrasts with an unusually high degree of HTT interspecific variation. While the impacts of conflict and domestication are often invoked to explain HTT variation, the telomeres are unstable structures such that neutral mutational processes and evolutionary tradeoffs may also dri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 104 publications
(114 reference statements)
1
6
0
Order By: Relevance
“…Studies carried out in flies bearing TDs as well as in somatic cells revealed that transposition events are regulated at different levels and involve distinct classes of regulators: a) cis-acting factors b) telomere capping proteins c) chromatin factors d) DNA repair proteins and e) still-uncharacterized genetic factors. The evidence that the majority of regulators are factors that are not encoded by telomeric retroelements supports the view of a host-transposon mutualisticinteraction that reduces the cost to the host of transposon activity[17,61,62]…”
supporting
confidence: 57%
See 3 more Smart Citations
“…Studies carried out in flies bearing TDs as well as in somatic cells revealed that transposition events are regulated at different levels and involve distinct classes of regulators: a) cis-acting factors b) telomere capping proteins c) chromatin factors d) DNA repair proteins and e) still-uncharacterized genetic factors. The evidence that the majority of regulators are factors that are not encoded by telomeric retroelements supports the view of a host-transposon mutualisticinteraction that reduces the cost to the host of transposon activity[17,61,62]…”
supporting
confidence: 57%
“…Finally, the acquisition of Het-A, TART and TAHRE at telomeres of mitotic chromosomes might rely more on recombination and/or gene conversion events rather than on transposition. Both events indeed account for telomere healing and de novo telomere formation that frequently occur in natural populations [60,61], which underscore their importance in telomere maintenance. It is worth noting that recombination between chromosome end sequences is at the base of the Alternative Lengthening of Telomeres (ALT) pathway that a subset of cancers uses to elongate their telomeres in order to prevent the telomere shortening normally occurring in proliferating cells [138].…”
Section: Telomeric Transposon Silencing and Telomere Protection: Convmentioning
confidence: 80%
See 2 more Smart Citations
“…More generally, repetitive elements can play important roles in many molecular and cellular mechanisms, and as a source of genetic variability (Bourque et al., 2018). They have contributed to evolutionary novelty in many organismal groups, by giving rise to important evolutionary features such as the mammalian placenta (Emera & Wagner, 2012), the vertebrate adaptive immune system (Kapitonov & Koonin, 2015; Zhang et al., 2019) and other telomere repair systems (Levis et al., 1993; McGurk et al., 2019). Thus, having genome assemblies that are as complete as possible facilitates research into a multitude of molecular phenomena (Slotkin, 2018).…”
Section: Introductionmentioning
confidence: 99%